"I couldn't have done it on my own." Perspectives of patients preparing for discharge from a UK high secure hospital. Issue 1 (5th March 2014) - Ann Sheryl Madders, Sarah; Amanda George, Cheryl
Abstract : Purpose: – Discharge preparation from high to medium levels of security has received little attention from researchers to date, but is a critical stage in a patient's pathway. This paper aims to capture the perspectives of patients who are preparing to move on from high to medium security. Design/methodology/approach: – Nine patients who were in the "discharge preparation" stage of their pathway were interviewed to capture their perspectives on the process. Interview transcripts were analysed using thematic analysis. Findings: – Nine themes were identified as representing the patient interviews: trust and support, feeling empowered, journey of self-acceptance, skilling-up, getting to know the Medium Secure Unit (MSU), feeling disempowered and unvalued, issues with the system, anxiety about endings, and stigma and society. Originality/value: – This paper gives voice to patients across clinical directorates at a UK high secure hospital regarding their perspectives on what has helped and hindered their discharge preparation. It presents some new findings, and recommended good practice, which should be of use to clinicians and managers who wish to enhance discharge preparation interventions for patients within high secure services.